Implications of Legislation on the Status of Children Born from Marriages That are Not Recorded in the Law - A. Ismail, Moh. Dhiwa Ulfajri (Universitas Negeri Gorontalo, 2023)
The issue of child protection has become the main concern of the government in recent years. The challenges of child protection are very diverse, ranging from poverty, ownership of birth certificates, child participation to violence against children. Related to children's civil rights, in the form of basic rights to obtain birth certificate documents. If the child does not have proof of identity, his whereabouts are not recognized by the state. In fact, children cannot access educational facilities, health care, social assistance, and other vital services. The consequence of not having a birth certificate makes it difficult to prove the legal identity of the child. When both parents get into trouble in court, the rights of the child are always neglected because they cannot prove that they are legitimate children in the eyes of the parents.law. The purpose of this researchTo find out and analyze the perspective of laws and regulations on the legal status of children born from unregistered marriages. This study uses a sociological juridical research method with a descriptive qualitative research approach and interactive analysis techniques.